2018
DOI: 10.1038/s41598-018-27612-w
|View full text |Cite
|
Sign up to set email alerts
|

A rapid method for assessing the accumulation of microplastics in the sea surface microlayer (SML) of estuarine systems

Abstract: Microplastics are an increasingly important contaminant in the marine environment. Depending on their composition and degree of biofouling, many common microplastics are less dense than seawater and so tend to float at or near the ocean surface. As such, they may exhibit high concentrations in the sea surface microlayer (SML – the upper 1–1000 μm of the ocean) relative to deeper water. This paper examines the accumulation of microplastics, in particular microfibres, in the SML in two contrasting estuarine syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…Suspected microplastic morphology was, as in the previous study utilising the same sampling method 8 , dominated by fibres (> 99%). As such, only fibres are presented in the data here.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Suspected microplastic morphology was, as in the previous study utilising the same sampling method 8 , dominated by fibres (> 99%). As such, only fibres are presented in the data here.…”
Section: Discussionsupporting
confidence: 65%
“…As such, only fibres are presented in the data here. As for the previous study 8 , it may be that the presence of sediment and organic material on the filters obscured microplastics of different shapes. The sampling technique may also have influenced the microplastics sampled, as previous studies in the open ocean found an effect of the SML sampling technique used on the abundance of various shapes of microplastic in the SML 29 .…”
Section: Discussionmentioning
confidence: 50%
“…Depending on their composition and degree of biofouling, many common microplastics are less dense than seawater so tend to float at or near the ocean surface, and as such may exhibit high concentrations in the upper ocean relative to deeper water. Manta trawls are used near the surface and a number of methods are available for sampling in the 1-1,000 µm surface microlayer, including rapid and facile glass plate sampling methods, which collect samples that contain relatively small amounts of sediment and biogenic material, facilitating subsequent microplastics identification (Anderson et al, 2018).…”
Section: Samplers and Subsequent Analyticsmentioning
confidence: 99%
“…In comparison with our study area,Lusher et al (2013) reported that 37% of fish in the English Channel had ingested MP, whereas this ingestion was only 5.4% in the southern North Sea(Foekema et al 2013). The high occurrence of MP in estuarine fish suggests that MP are more common within estuarine water column and sediments than in the marine environment(Anderson et al 2018). These transitory waters are important transport routes of MP into the marine environment since about 80% of marine plastics are derived from land-based anthropogenic sources(Andrady 2011;Schmidt et al 2017).…”
mentioning
confidence: 55%